como revolver essa equação literal?
Anexos:
![](https://pt-static.z-dn.net/files/dcf/8c8ccc306a98dfaddc68c1451ca6a70d.jpg)
Soluções para a tarefa
Respondido por
1
equação literal
(x - a)/(a + 1) - (x + a)/(a - 1) = 2/(a² - 1)
mmc = a² - 1
(a - 1)*(x - a) - (a + 1)*(x + a) = 2
ax - a² - x + a - ax - a² - x - a = 2
-2a² - 2x = 2
a² + x = -1
x = -1 - a²
Perguntas interessantes
Artes,
10 meses atrás
Filosofia,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Saúde,
1 ano atrás